Fabrication and characterization of gold nano-gaps for ssDNA immobilization and hybridization detection - T.S., Dhahi; Uda, Hashim, Prof. Dr.; N.M., Ahmed; H., Nazma (Journal of New Materials for Electrochemical Systems, 2011)
Link to publisher's homepage at http://www.groupes.polymtl.ca/jnmes/